Pengaruh Mekanisme Corporate Governance, Bonus Plans, Debt coveant dan Ukuran Perusahaan Terhadap Manajemen Laba - Marfuah Marfuah; Himawan Yogatama (Jurnal Aplikasi Bisnis, 2017)
The purpose of this study was to examine the effect of corporate governance mechanisms, bonus plans, debt covenants andfirm size on earnings management. Corporate governance mechanisms in this study was measured using four variables, namely the concentration of ownership, independent commissioners, audit committee and auditor reputation. 93 samples cre selected by purposip sampling the observation period of 2009 through 2011.Four corporate governance variables thought to have a negative impact on earnings management, while the variable bonus plans, debt covenants and firm size has a positive influence on earnings management. Based on regression analysis found that the two corporate governance variables, namely the significant the level earnings concentration of ownership and auditor reputation as predicted negativeeffecton earnings management. This indicates that the high of concentration of ownership and auditor reputation, then the management measures will decrease. While testing the variable audit committee and independent commissioners found results inconsistent with previous predictions. The audit committee has a significant positive effect on earnings management, while independent dire commissioners has no significant negative impact on earnings management.The test results ofthe other three variables, namely bonus plans, debt covenants and the size of the company shows that the only variable bonus plans that have a significant positive effect on earnings management. Thh indicates that earnings management tends to occur in companies that have a bonus scheme, because managers tend to perform actions that manage earnings to maximize bonuses they receive.